2022
DOI: 10.1002/ps.7225
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the lethal and sub‐lethal effects of genetically modified soybean expressing Cry1A.105, Cry2Ab2, and Cry1Ac insecticidal proteins against Spodoptera species (Lepidoptera: Noctuidae) in Brazil

Abstract: BACKGROUND MON 87701 × MON 89788 × MON 87751 × MON 87708 soybean, that expresses Cry1A.105, Cry2Ab2, and Cry1Ac insecticidal proteins and confers tolerance to glyphosate and dicamba, is a potential tool for managing Spodoptera species in soybean fields in Brazil. In this study, we characterized the lethal and sub‐lethal effects of Cry1A.105/Cry2Ab2/Cry1Ac soybean against Spodoptera species and genotypes of Spodoptera frugiperda resistant and susceptible to Cry1 and Cry2 proteins. These evaluations were also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…These parameters coincide with studies where other lepidopterans experienced alterations in their developmental parameters when ingesting Bt proteins (Pérez-Hedo et al 2011,Barcellos et al 2023). Sublethal doses of Bt can induce an increase in the weight of the larvae, as was observed in the Rnu-SE population, coinciding with studies carried out on Spodoptera eridania (Stoll), there was an effect of hormesis at lower doses of the Cry1Ac toxin(Rabelo et al 2020).…”
supporting
confidence: 85%
“…These parameters coincide with studies where other lepidopterans experienced alterations in their developmental parameters when ingesting Bt proteins (Pérez-Hedo et al 2011,Barcellos et al 2023). Sublethal doses of Bt can induce an increase in the weight of the larvae, as was observed in the Rnu-SE population, coinciding with studies carried out on Spodoptera eridania (Stoll), there was an effect of hormesis at lower doses of the Cry1Ac toxin(Rabelo et al 2020).…”
supporting
confidence: 85%
“…This genetically modified (GM) soybean confers protection against Anticarsia gemmatalis (Hübner, 1818) (Lepidoptera: Erebidae) and against Chrysodeixis includens (Walker, [1858]), Chloridea virescens (Fabricius, 1781) and Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) [ 4 , 5 , 6 , 7 , 8 ] and is cultivated on more than 36 million hectares per season in Brazil [ 9 ]. During the 2021/2022 season, the event MON 87751 × MON 87708 × MON 87701 × MON 89788 (trade name Intacta 2 Xtend ® ), expressing Cry1A.105, Cry2Ab2 and Cry1Ac proteins, was also released for commercial use in Brazil, extending the protection conferred by Bt soybean to the species S. cosmioides [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have stated that Cry1A.105/Cry2Ab2/Cry1Ac and Cry1Ac soybean technologies had reduced lethality against S. eridania and S. frugiperda [ 5 , 8 , 10 ]. This can be explained by the naturally low susceptibility of these species to Bt proteins [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Except for S. frugiperda, no larvae of the tested Spodoptera species developed into adults on this soybean type. Results from previous studies also showed that no larvae of S. cosmioides, S. albula or S. eridania were able to develop to the adult stage on Cry1A.105/Cry2Ab2/Cry1Ac soybean [10]. Nonetheless, none of the L1 and L2 larvae of Spodoptera species surviving on Cry1A.105/Cry2Ab2/Cry1Ac soybean for 10 d (∼40% for S. frugiperda and <20% for other species tested) survived until the adult stage when exposed to leaves sprayed with flubendiamide or thiodicarb at the field label dose or 50% of this dose.…”
Section: Discussionmentioning
confidence: 86%